Perancangan Sistem Informasi Akuntansi Persediaan Barang Dagang Pada Toko Rianzi Menggunakan PHP Dan MySQL - Putri Permata Sari; Liana Liana; Nurliza Lubis (Jurnal Riset Ekonomi dan Akuntansi, 2024)
the aim of this research is to determine the merchandise inventory accounting information system used by Toko Rianzi. This research method uses descriptive research by looking for theoretical research related to the merchandise inventory accounting information system. The data collection used was observation and interviews. The type of data used is quantitative data. The results of this research are expected to provide information regarding the merchandise inventory accounting information system. The design of this merchandise inventory accounting information system uses the system development method Dynamic System Development Method with 3 main stages, namely, before the project, project life cycle and after the project. As well as 5 sub stages (feasibility study, business study, model iteration, iteration design, manufacture and implementation). Discussion of design researchThis merchandise inventory accounting information system is expected to be able to makes it easier for Toko Rianzi to make inventory reports and financial reports.